Conformal field theory, boundary conditions and applications to string theory - Schweigert, Christoph; Fuchs, Jürgen; Walcher, Johannes (Arxiv, 2000)
This is an introduction to two-dimensional conformal field theory and its applications in string theory. Modern concepts of conformal field theory are explained, and it is outlined how they are used in recent studies of D-branes in the strong curvature regime by means of CFT on surfaces with boundary.